Optimización del sistema de gestión de cotizaciones en la microempresa Pablo construcciones a través del desarrollo de un sistema automatizado excel para minimizar el tiempo de entrega de las cotizaciones. - Condor Quillupangui, Michael Xavier (2023)
Globalization has generated high competition between micro, small and medium-sized companies in all fields of work, where the metal-mechanic sector is not far behind, since they seek to offer and gain a share of the market with their products and services. This research project identified the problem in the "Pablo Construcciones" microenterprise, which consists in the fact that the quote management process is carried out manually and does not have the necessary control, causing loss of customers due to the delay in the delivery time of a quote.